An evaluation of single and mixed gender computer science classes - Andrea Maria Weber (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2007)
Discussions on the benefits of single-gender education on girls' science outcomes are popular in the German education literature. However, most empirical evidence tends to be qualitative work and the causal effects of single-gender education are hardly identified using appropriate statistical methods. This paper provides insights from a recent single-gendereducation school project conducted in computer science classes at a German lower secondary school. About 80 students participated in this intervention study repeatedly answering specifically designed questionnaires and tests. The project fails to identify positive effects from single-gender education but the interpretation is impeded by several confounding factors. When directly asked, most students prefer to be educated in mixed-gender groups, while the participating teachers judge their teaching experience with the project groups in favour of singlegender education.
Keywords: I21; J16; 330; gender; education; identification; coeducation; segregation; experiments